Trade diversity and stages of development - Evidence on EU countries - Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
The paper presents the dynamics of trade diversity with respect to stages of development in the European context. The analysis focuses on EU27 countries observed across the years 1988-2010 and compared to a sample of 136 international economies at all levels of income per capita. We use product level statistics (six digit HS0) and confront export and import patterns of absolute diversification/concentration. The results show that in line with 'stages of diversification' approach (Imbs and Wacziarg, 2003), EU27 countries are characterized by high degree of trade diversity (on average, EU27 countries export 78% and import 90% of goods effectively exported and imported at the world level) and within the analyzed period most of them registered a reconcentration of trade structures. Obtained estimation results confirm positive relationship between trade diversity and economic development levels (conditional mainly upon the size of the country) with a possibility of reconcentration at higher stages of development (observable in nonparametric estimates).
Keywords: F14; O11; O52; 330; diversification; concentration; trade; economic development